2019
DOI: 10.1111/jtxs.12497
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of simultaneous addition of sucrose and xanthan effects on the thermal, pasting, and rheological behavior of corn starch

Abstract: Thermal, pasting, and rheological properties of starch-based systems are the key characteristics for its processing. This study aimed to investigate the main and interactive effects of sucrose and xanthan on the thermal, pasting, and rheological behavior of corn starch. A central composite design (CCD) was used to evaluate the effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Additionally, Zolelmein et al. (2020) found that the addition of xanthan gum and sucrose could improve the thermal stability of starch pastes by forming more hydrogen bonds. Pongsawatmanit et al.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zolelmein et al. (2020) found that the addition of xanthan gum and sucrose could improve the thermal stability of starch pastes by forming more hydrogen bonds. Pongsawatmanit et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies concerning the interaction of starch with salt [ 31 , 32 ], acids [ 33 ], sucrose [ 34 , 35 ], and other sweetening agents [ 36 , 37 , 38 ] seem to be of special importance, as they are common food components. A commonly observed phenomenon is the negative effect of acids on the thickening ability of starch.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of sucrose increases gelatinization temperature and enthalpy. These phenomena are accompanied by an increase of pasting and rheological parameters, as well as the strength of gels [ 35 ]. A similar effect is also caused by the presence of polyols, i.e., maltitol, sorbitol, xylitol, and mannitol.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects have been reported with soluble sugars and hydrocolloids. [28][29][30] The influence by flour/PSG reduction on the transition enthalpies of mixed cracker doughs was, however, insignificant except that F3 tended to display a higher value.…”
Section: Thermal Properties Of Cracker Doughs and Influences On Gelatinisationmentioning
confidence: 97%